More Than Meets the Eye: A Review and Future Directions for the Social Psychology of Socioemotional Wealth. (March 2018) - Jiang, David S.; Kellermanns, Franz W.; Munyon, Timothy P.; Morris, M. Lane
Socioemotional wealth (SEW) research has been criticized for not directly assessing the locus and drivers of family members' SEW. We propose that a social psychological approach to SEW can help address these concerns, conducting analyses on 421 articles published across 25 journals during the first decade of SEW research. We therefore assess how SEW has been used and identify various inherent complexities that SEW poses for researchers. Altogether, our analyses afford us opportunities to better understand SEW scholarship's social psychological roots and to propose an agenda that can help further build and extend the psychological microfoundations of family firms.